Tourismus als Entwicklungsfaktor im kubanischen Transformationsprozess - Wehrhahn, Rainer; Widderich, Sönke (ERDKUNDE, 2000)
In response to the economic collapse after the demise of COMECON, the Cuban government introduced various new economic policies. The aim of these measures was to generate revenue in hard currency and simultaneously to diversify the economy, which was extremely dependent on sugar exports, and rebuild the domestic economy. The most important strategy employed was to promote international tourism. To accomplish the desired goals the government permitted joint ventures, foreign direct investment and private economic activities and allowed individuals to possess foreign currency. This paper attempts to evaluate the consequences of this development strategy. It first investigates the economic effects and social impacts at the national level. Subsequently the interaction between tourism and urban renewal is illustrated, using the historic center of Havana as an example. On the whole the tourist boom of the past years reveals a positive economic balance, seen in relation to hard currency revenue and to secondary effects, e. g., on management, infrastructure, subcontracting industries and the labor market. Nevertheless, although the Cuban government continues to exercise extensive controls and both foreign investors and Cubans working in the tourism sector are subject to a great number of restrictions, there are serious social consequences. Cuban society is splitting up in two groups, one composed of persons who have access to foreign currency and the other of persons who are ’left out’. The result is a previously unknown polarization of the population, which is antithetical to the ideal of a socialist society.